Drawing the legal boundaries: addressing the crime of trafficking in persons in Peru under national and international law - Grandez Hidalgo, Jesús Andrés (2024)
In Peru, human trafficking still represents a serious risk for its female and child population. This scourge operates in a complex social environment, which is a constant challenge for our country. Tackling this crime is not only a challenge for the protection of human rights, but also poses significant national, and international security threats. This article seeks to explore the various facets of human trafficking, including its stages, modalities, and impacts on victims, while offering an introductory overview of the Peruvian context; it also reviews the national normative framework and the main international instruments related to human trafficking.